Modeling and optimization of mixing parameters using response surface methodology and characterization of palm oil clinker fine modified bitumen - Yaro, N.S.A. (Elsevier Ltd, 2021)
One of the major biomass wastes discarded in large volumes from the palm oil mill is the palm oil clinker (POC) chunks. Thus, the need to develop strategies to promotes cleaner production is crucial for environmental sustainability. The present study aims to ascertain the viability of using palm oil clinker fine (POCF) as a bitumen modifier to improve conventional properties. To achieve this aim response surface methodology (RSM) was utilized to evaluate the influence of POCF dosage and mixing parameters on the conventional properties (penetration, softening point, and penetration index) of the POCF-modified bitumen (POCF-MB). By utilizing the central composite design (CCD) process, a quadratic regression model was considered with a p-value < 5 for all responses at the globalize optimum conditions. ANOVA analysis reveals that POCF dosage and mixing time show a substantial effect on the bitumen's properties in comparison with the mixing speed and temperature. After optimization, the optimal POCF dosage was 7.75, and mixing parameters for temperature, speed, and time are 140 Â°C, 1000 rpm, and 51.9 min respectively. At optimum POCF dosage and mixing parameters, the percentage error between the RSM predicted and laboratory values was < 5 for all responses. The modification produces a stiffer bitumen blend, which causes a decrease in penetration with an increased softening point. Subsequently, the characterization of the POCF-MB blend was assessed for the multi-objective optimization optimum input parameters via Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and Scanning electron microscope/energy dispersive x-ray (SEMEDX). Results of characterization show that POCF significantly influences the bitumen's conventional properties. The study findings show that POCF has great potential as an alternative bitumen modifier to promote sustainability. Â© 2021 Elsevier Ltd